Novel exon of mammalian ADAR2 extends open reading frame. - Stefan Maas; Willemijn M Gommans (PLoS ONE)
Background The post-transcriptional processing of pre-mRNAs by RNA editing contributes significantly to the complexity of the mammalian transcriptome. RNA editing by site-selective A-to-I modification also regulates protein function through recoding of genomically specified sequences. The adenosine deaminase ADAR2 is the main enzyme responsible for recoding editing and loss of ADAR2 function in mice leads to a phenotype of epilepsy and premature death. Although A-to-I RNA editing is known to be subject to developmental and cell-type specific regulation, there is little knowledge regarding the mechanisms that regulate RNA editing in vivo. Therefore, the characterization of ADAR expression and identification of alternative ADAR variants is an important prerequisite for understanding the mechanisms for regulation of RNA editing and the causes for deregulation in disease. Methodology/principal findings Here we present evidence for a new ADAR2 splice variant that extends the open reading frame of ADAR2 by 49 amino acids through the utilization of an exon located 18 kilobases upstream of the previously annotated first coding exon and driven by a candidate alternative promoter. Interestingly, the 49 amino acid extension harbors a sequence motif that is closely related to the R-domain of ADAR3 where it has been shown to function as a basic, single-stranded RNA binding domain. Quantitative expression analysis shows that expression of the novel ADAR2 splice variant is tissue specific being highest in the cerebellum. Conclusions/significance The strong sequence conservation of the ADAR2 R-domain between human, mouse and rat ADAR2 genes suggests a conserved function for this isoform of the RNA editing enzyme.